Influence of different plant populations and fertilization in associated system of maize and bean - Lima, João Maria Pinheiro de; Lima, Luiz Augusto de Paula; Andrade, Luiz Antonio de Bastos; Rezende, Pedro Milanez de (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment involving monocultures of common bean (Phaseolus vulgaris L.) and maize (Zea mays L.) and the association of these crops was carried out at the Escola Superior de Agricultura de Lavras, Minas Gerais State, Brazil, during the agricultural year 1982/83 with the principal objective of studying the effect of different populations of bean, fertilized and nonfertilized in two systems of cultivation, and their effects on maize an bean. The experimental desing used was randomized blocks in a 5 x 2 factorial, consisting of treatments: five populations of common bean planted between the rows of maize, both fertilized and non-fertilized, with four additional treatment for common bean and three for maize and four replications. It was verified that the production of common bean, when associated, was a direct function of the planting system and the fertilization. The presence of common bean independent of the populations studied and of the presence of fertilizers, did not affect the maize, the production of common bean in association thereby constituting an advantage in economic terms. The results obtained also indicated the necessity of determining the optimum level of fertilization for the mayze-bean association.